ANALISIS PENERIMAAN ZOOM MEETING SEBAGAI MEDIA PEMBELAJARAN DENGAN PENDEKATAN UTAUT2 DAN VARIABEL AUTONOMY - Prambodo, Yoga Listi; Sharyanto, Sharyanto; Saputro, Joko (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study analyzes the acceptance of the Zoom Meeting teleconference media by integrating the Autonomy variable into the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The research was conducted at STT Wastukancana Purwakarta with 330 respondents consisting of active students and lecturers. Using a quantitative approach with purposive sampling, data were collected through online questionnaires and processed using SmartPLS. The results show that all UTAUT2 constructs—Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, and Habit—significantly influence Behavioral Intention to use Zoom Meeting as a learning medium. Moreover, Autonomy has a positive and significant effect on Effort Expectancy, Performance Expectancy, and Behavioral Intention, indicating that the higher the autonomy of users in the learning process, the greater their acceptance of teleconference technology. This study confirms that the integration of Autonomy into the UTAUT2 model strengthens the theoretical understanding of user acceptance behavior in online learning environments during and after the COVID-19 pandemic.